Influence of rhizobial inoculation on photosynthesis and grain yield of rice - Peng, Shaobing; Biswas, Jatish C.; Ladha, Jagdish K.; Gyaneshwar, Prasad; Chen, Yizhu (Wiley, 2002)
Rhizobial inoculation increases grain yield in rice (Oryza sativaL.), a nonlegume plant, but little is known about the mechanism(s) involved. This study was conducted to determine whether inoculation with rhizobia could influence leaf photosynthesis of rice plants under greenhouse conditions. Rice seeds and pot soil were inoculated with three rhizobial strains with or without added N fertilizer. Single‐leaf net photosynthetic rates were measured with portable photosynthesis systems (LI‐6200 and LI‐6400) at several growth stages. Stomatal conductance, chlorophyll fluorescence, specific leaf weight, and leaf N content were also measured. Grain yield and yield components were determined at maturity. A significant increase in single‐leaf net photosynthetic rate by rhizobial inoculation was observed in all three independent experiments. The effect of rhizobial inoculation on photosynthesis was greater in zero‐N than in 90 kg N ha−1treatment. The increase in photosynthetic rate by rhizobial inoculation was 12% averaged across all treatments in the three experiments. The effects of rhizobial inoculation on stomatal conductance, specific leaf weight, and leaf N content were relatively small and less consistent than photosynthetic rate. Chlorophyll fluorescence data suggest that the increase in photosynthetic rate following rhizobial inoculation was not associated with conversion efficiency of light energy in photosystem II. Rhizobial inoculation increased grain yield by 16%. The increase in grain yield was due to an increase in total biomass production rather than harvest index. These results suggest that certain strains of rhizobia can promote rice growth and yield through mechanisms that improve single‐leaf net photosynthetic rate.